The Use of YouTube to Enhance Learners’ English Listening Skills - Khairat, Nurul (Surakarta English and Literature Journal, 2024)
In recent years, YouTube has become an important platform for educational content. While various studies have examined YouTube’s role in improving learners’ English listening skills, much of the earlier research focused on outdated versions of the platform. This study aims to update these findings by analyzing more recent studies and addressing gaps in the literature regarding YouTube’s impact on enhancing English listening skills. The review includes nineteen studies published between 2020 and 2024, with one additional study from 2014, sourced from Google Scholar and the International Journal. The results show that YouTube provides authentic language resources, like podcasts, videos, and interviews, which significantly boost listening comprehension. However, the effectiveness of YouTube as a learning tool depends on the use of effective strategies, including customized playlists, guided viewing, and interactive exercises. The study also identifies challenges such as limited internet access and the necessity of pedagogical oversight to fully utilize YouTube’s benefits. Although YouTube holds promise as a resource for language learning, further research is needed to assess its impact on academic performance and long-term language development. This study offers practical advice for educators looking to incorporate YouTube into their teaching methods.